Enhancing learning activity and learning outcomes through virtual reality–based learning media in office management education - Rahmawati, Vera Eka; Churiyah, Madziatul; Arief, Mohammad; Kusdiyanti, Heny (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
Rapid technological advancements have significantly transformed educational practices, particularly in the integration of digital learning media. This research and development study aims to produce and evaluate Virtual Reality (VR)–based learning media for the “Office Technology Equipment and Applications” component in Office Management and Business Services education. The study employs the ADDIE development model—analysis, design, development, implementation, and evaluation—and involves material experts, media experts, and Grade X students from SMK Negeri 1 Turen, East Java. Qualitative data were collected from expert feedback, while quantitative data were obtained through validation sheets, user trials, learning activity observations, and assessments of students’ cognitive and psychomotor learning outcomes. Validation results indicated that the VR-based learning media achieved an average feasibility score of 97% from both material and media experts, categorized as “highly valid.” Small-group trials also demonstrated very high practicality and positive student responses. Experimental implementation further revealed a substantial improvement in learning activity, particularly in emotional, visual, and mental engagement. Independent sample t-tests confirmed significant differences in cognitive and psychomotor learning outcomes between the experimental and control groups (p < 0.05), with the experimental group achieving higher scores. The findings demonstrate that VR-based learning media effectively enhance students’ engagement and mastery of learning materials by providing immersive and interactive virtual environments that simulate real-world office settings. This study highlights the potential of VR technology to support innovative learning strategies and recommends its broader implementation in vocational education to promote active learning and improved learning outcomes.